A comparative study of leachate quality and biogas generation in simulated anaerobic and hybrid bioreactors. (July 2015) - Xu, Qiyong; Tian, Ying; Wang, Shen; Ko, Jae Hac
Highlights: Temporary aeration shortened the initial acid inhibition phase for methanogens. COD decreased faster in the hybrid bioreactor than that in the anaerobic control. Methane generations from hybrid bioreactors were 133.4 L/kgvs and 113.2 L/kgvs . MSW settlement increased with increasing the frequency of intermittent aeration. Abstract: Research has been conducted to compare leachate characterization and biogas generation in simulated anaerobic and hybrid bioreactor landfills with typical Chinese municipal solid waste (MSW). Three laboratory-scale reactors, an anaerobic (A1) and two hybrid bioreactors (C1 and C2), were constructed and operated for about 10 months. The hybrid bioreactors were operated in an aerobic–anaerobic mode with different aeration frequencies by providing air into the upper layer of waste. Results showed that the temporary aeration into the upper layer aided methane generation by shortening the initial acidogenic phase because of volatile fatty acids (VFAs) reduction and pH increase. Chemical oxygen demand (COD) decreased faster in the hybrid bioreactors, but the concentrations of ammonia–nitrogen in the hybrid bioreactors were greater than those in the anaerobic control. Methanogenic conditions were established within 75 d and 60 d in C1 and C2, respectively. However, high aeration frequency led to the consumption of organic matters by aerobic degradation and resulted in reducing accumulative methane volume. The temporary aeration enhanced waste settlement and the settlement increased with increasing the frequency of aeration. Methane production was inhibited in the anaerobic control; however, the total methane generations from hybrid bioreactors were 133.4 L/kgvs and 113.2 L/kgvs . As for MSW with high content of food waste, leachate recirculation right after aeration stopped was not recommended due to VFA inhibition for methanogens.